Low-Power Absorption Saturation in Semiconductor Metasurfaces - Zubyuk, Varvara V.; Vabishchevich, Polina P.; Shcherbakov, Maxim R.; Shorokhov, Alexander S.; Fedotova, Anna N.; Liu, Sheng; Keeler, Gordon; Dolgova, Tatyana V.; Staude, Isabelle; Brener, Igal; Fedyanin, Andrey A. (ACS Photonics, 2019)
Saturable optical elements lie at the cornerstone of many modern optical systems. Regularly patterned quasi-planar nanostructures - metasurfaces - are known to facilitate nonlinear optical processes. Such subwavelength semiconductor nanostructures can potentially serve as saturable components. Here we report on the intensity-dependent reflectance of femtosecond laser pulses from semiconductor metasurfaces with Mie-type modes, caused by the absorption saturation. Arrays of GaAs nanocylinders with magnetic dipole resonances in the spectral vicinity of the GaAs bandgap demonstrate a reduced saturation intensity and increased self-modulation efficiency, an order of magnitude higher than bulk GaAs or unstructured GaAs films. By contrast, the reflection modulation is shown to be negligible in the CW regime for the same average intensities, indicating that the process is not the result of temperature effects. Our work provides a novel idea for low-power saturable elements based on nonthermal nature of saturation. We conclude by devising a high-quality metasurface that can be used, in theory, to further reduce the saturation fluence below 50 nJ/cm2.
CRIS-Team Scopus Importer:2023-04-20
Keywords: absorption saturation; I-scan; Mie-type resonance; semiconductor metasurfaces